2021
DOI: 10.1128/mra.01011-21
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of Bacillus pacificus KVCMST-8A-12, Isolated from a Marine Sediment Sample from the Kanyakumari Coast, India

Abstract: A DNase-producing Bacillus pacificus strain was isolated, and the whole-genome sequence is reported in this paper. The draft genome sequence of Bacillus pacificus KVCMST-8A-12 constitutes 2.4 Gbp of raw reads, with a GC content of 35.24%. In total, 5,661 protein-coding genes, 64 tRNA genes, and 4 rRNA genes were predicted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Interestingly, as a biocontrol agent and a biostimulator and biofertilizer bacterium, B. thuringiensis could promote plant growth (Azizoglu, 2019;Raddadi et al, 2007). B. pacificus is an endophytic bacterium that modulates plant growth promotion and induces plant systemic resistance (Sahu et al, 2020), whereas this species is reported to produce extracellular DNase, which can be commercially exploited (Santhi et al, 2021). In this study, B. cereus, B. thuringiensis, and…”
Section: F I G U R Ementioning
confidence: 86%
See 1 more Smart Citation
“…Interestingly, as a biocontrol agent and a biostimulator and biofertilizer bacterium, B. thuringiensis could promote plant growth (Azizoglu, 2019;Raddadi et al, 2007). B. pacificus is an endophytic bacterium that modulates plant growth promotion and induces plant systemic resistance (Sahu et al, 2020), whereas this species is reported to produce extracellular DNase, which can be commercially exploited (Santhi et al, 2021). In this study, B. cereus, B. thuringiensis, and…”
Section: F I G U R Ementioning
confidence: 86%
“…B . pacificus is an endophytic bacterium that modulates plant growth promotion and induces plant systemic resistance (Sahu et al, 2020), whereas this species is reported to produce extracellular DNase, which can be commercially exploited (Santhi et al, 2021). In this study, B .…”
Section: Discussionmentioning
confidence: 99%